Machine Learning Meets Cybersecurity - J. P. Pramod; Baddula Gayathri Yadav; Sumaiyya Fatima (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In an era where digital transformation is accelerating, the integration of machine learning (ML) into cybersecurity is becoming increasingly crucial. This article delves into the significant role that ML plays in enhancing cybersecurity measures. ML’s ability to process and analyze vast amounts of data at unprecedented speeds allows for more efficient threat detection, anomaly identification, and predictive analytics. These capabilities are essential in pre-empting and mitigating cyber threats in real-time. However, the same technologies that bolster defences are also being leveraged by cybercriminals to develop more sophisticated attacks, posing unique challenges. This article explores the dual-edged nature of ML in cybersecurity, highlighting both its benefits and the potential risks. It discusses the challenges of bias in ML algorithms, the vulnerabilities exposed through adversarial attacks, and the ethical and privacy considerations that come with deploying ML solutions. Furthermore, it provides insights into the future trends and developments in ML-driven cybersecurity and underscores the importance of synergizing human expertise with machine intelligence to build more resilient cybersecurity frameworks. Through this exploration, the article aims to provide a comprehensive understanding of the transformative impact of ML on cybersecurity and the path forward in addressing the accompanying challenges.